2016
DOI: 10.1074/mcp.o115.055350
|View full text |Cite
|
Sign up to set email alerts
|

An Inducible Retroviral Expression System for Tandem Affinity Purification Mass-Spectrometry-Based Proteomics Identifies Mixed Lineage Kinase Domain-like Protein (MLKL) as an Heat Shock Protein 90 (HSP90) Client

Abstract: Tandem affinity purification–mass spectrometry (TAP-MS) is a popular strategy for the identification of protein–protein interactions, characterization of protein complexes, and entire networks. Its employment in cellular settings best fitting the relevant physiology is limited by convenient expression vector systems. We developed an easy-to-handle, inducible, dually selectable retroviral expression vector allowing dose- and time-dependent control of bait proteins bearing the efficient streptavidin-hemagglutini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 67 publications
1
13
1
Order By: Relevance
“…Fundamental differences between the mouse and human necroptosis pathways are not altogether surprising considering 71.5%, 60.5%, and 61% amino acid identity between mouse and human RIPK1, RIPK3, and MLKL, respectively, and the inability of human MLKL to reconstitute the necroptosis pathway in mouse Mlkl −/− fibroblasts 7 . However, the inability of hMLKL PsKD mutants to induce cell death in our study was surprising in light of previous reports 2 , 12 , 18 , 30 32 . The basis for these differences are unclear, although it is possible that the choice of cell line, expression vector, and mode, and whether endogenous MLKL is present, are contributing factors.…”
Section: Discussioncontrasting
confidence: 79%
“…Fundamental differences between the mouse and human necroptosis pathways are not altogether surprising considering 71.5%, 60.5%, and 61% amino acid identity between mouse and human RIPK1, RIPK3, and MLKL, respectively, and the inability of human MLKL to reconstitute the necroptosis pathway in mouse Mlkl −/− fibroblasts 7 . However, the inability of hMLKL PsKD mutants to induce cell death in our study was surprising in light of previous reports 2 , 12 , 18 , 30 32 . The basis for these differences are unclear, although it is possible that the choice of cell line, expression vector, and mode, and whether endogenous MLKL is present, are contributing factors.…”
Section: Discussioncontrasting
confidence: 79%
“…Here we observed that fusion to the mouse PsK domain was sufficient to enable the h4HB + brace, but not the h4HB alone, to kill MDFs. These findings indicate that the mMLKL PsK domain may function as a protein interaction domain to recruit host factors that contribute to necroptosis signalling, akin to the role reported for the co-chaperone system, HSP90:Cdc37, in MLKL activation [31,35,36]. The h4HB-hBrace-mPsK construct constitutively killed Ripk3 -/-Mlkl -/fibroblasts, therefore the constitutive oligomerisation observed by BN-PAGE, and killing activity of this construct cannot be explained by constitutive activation by RIPK3.…”
Section: Discussionmentioning
confidence: 76%
“…To date, aside from the upstream regulator kinase RIPK3, few MLKL interactors have been identified. While the HSP90-Cdc37 cochaperones have been implicated in MLKL activation (25,36,37), the underlying mechanism is unclear, and such an interaction would be expected to be mediated via the MLKL pseudokinase domain, and not the 4HB domain, because HSP90 and Cdc37 are best characterized as cochaperones for protein kinases and pseudokinases (38). Similarly, the recent implication of TAM kinases in promotion of MLKL-mediated cell death is likely to be a distinct process because the reported substrate residue, Y376, is located in the pseudokinase domain, rather than the NTR.…”
Section: Discussionmentioning
confidence: 99%